Heart failure with reduced ejection fraction: A literature review on epidemiological profile and care strategies (Research, Society and Development, 2025)
Heart failure is one of the cardiovascular diseases with the most pronounced morbidity profile and increasing prevalence, making it a major public health problem. The overall objective of this review is to analyze and synthesize current scientific knowledge on the epidemiological profile, pathophysiology, and treatment strategies for Reduced Ejection Fraction Heart Failure (RIHF), with an emphasis on the social determinants of health, highlighting the pharmacological and non-pharmacological treatment of RIHF according to current guidelines. This is an exploratory-descriptive study. The bibliographic search was conducted in publicly accessible electronic databases, including Google Scholar, SciELO (Scientific Electronic Library Online), and the UpToDate clinical reference tool. Data collection was carried out in August 2024 and included publications from the last five to ten years, prioritizing more recent articles, guidelines, and systematic reviews to ensure the relevance of the information. It is evident that addressing the Social Determinants of Health (SDH) in the management of patients with heart failure (HF) is necessary. Factors such as limited access to resources, low health literacy, and financial problems add stress, compromise self-care, and reduce access to quality care, impacting prognosis. It becomes imperative that the care of reduced ejection fraction (HFrEF) transcends pharmacological treatment (the "quadruple therapy" using SGLT2 inhibitors) and incorporates active strategies to mitigate the impact of SDH, such as health education programs and active patient outreach.